PEREMPUAN KEPALA KELUARGA DAN PENCARI NAFKAH DI PASAR BARUGA KOTA KENDARI DALAM PERSPEKTIF HUKUM ISLAM - Asni Asni (Institut Agama Islam Negeri Kendari, 2017)
This study focuses on the role of women as a head of a family, especially who work as a trader in Baruga Market of Kendari to fulfill their families’ needs. This research is a descriptive qualitative study. The data are collected from the interviews of the widows and the head of the Baruga Market, complemented by the results of observation on the activities of the widows in the market. The results indicate that the widows have a very significant role to finance their family. In the Islamic law perspective, this is relevant to aspects of maintenance of offspring as part of the maqasid al-shari'a theory. On the other hand, they have many problems, such as, employment, social, economic problems and the problems related to their families. While the strategies to solve their problems are creating a work motivation, organize family expenses, maintain good relations with the others, do marketing strategy and manage the time between family and work affairs. The implications of this research are the need for special attention from the government, social organizations and society to women as a head of a family and the need to strengthen their position by the state on a normative side and in terms of policies that could improve their lives